Management of character learning based on islamic education: a literature review - Ali Ramatni; Tenggo Husnul Fata; Surajiyo Surajiyo (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2025)
This study aims to explore the management of character learning based on Islamic education through a qualitative literature review. Scholarly sources were selected systematically based on relevance to key Islamic educational principles and character development practices, with 30 primary sources meeting criteria of recency and academic rigor. The development of character education rooted in Islamic teachings, particularly in the concepts of akhlaq (morality), adab (manners), and tarbiyah (holistic education), is essential in shaping the moral and ethical values of students. This review identifies successful practices within Islamic educational institutions, such as integrating Quranic teachings and prophetic traditions into curricula, and underscores the critical roles of teachers, parents, and administrators in modeling and reinforcing Islamic character values. Notably, the research highlights challenges in implementing consistent character education amid pressures of secularization and globalization. Findings suggest that a comprehensive management approach—one that aligns pedagogy, curriculum, and community engagement with Islamic values—is needed. This includes clear guidelines on educator roles and stakeholder involvement, as well as institutional support mechanisms. The study advances the literature by analyzing gaps in current approaches to Islamic character education and by recommending specific strategies for enhancing management practices. Further research is suggested to test these insights in various educational contexts to refine implementation strategies and strengthen the impact of Islamic character education.